Co-localization of LTBP-2 with FGF-2 in fibrotic human keloid and hypertrophic scar - Mohamed Sideek, Mohamed Arshad; Teia, Abdulrahman; Kopecki, Zlatko; Cowin, Allison J.; Gibson, Mark A. (Springer Netherlands, 2016)
We have recently shown that Latent transforming growth factor-beta 1 binding protein-2 (LTBP-2) has a single high-affinity binding site for fibroblast growth factor-2 (FGF-2) and that LTBP-2 blocks FGF-2 induced cell proliferation. Both proteins showed strong co-localisation within keloid skin from a single patient. In the current study, using confocal microscopy, we have investigated the distribution of the two proteins in normal and fibrotic skin samples including normal scar tissue, hypertrophic scars and keloids from multiple patients. Consistently, little staining for either protein was detected in normal adult skin and normal scar samples but extensive co-localisation of the two proteins was observed in multiple examples of hypertrophic scars and keloids. LTBP-2 and FGF-2 were co-localised to fine fibrous elements within the extracellular matrix identified as elastic fibres by immunostaining with anti-fibrillin-1 and anti-elastin antibodies. Furthermore, qPCR analysis of RNA samples from multiple patients confirmed dramatically increased expression of LTBP-2 and FGF-2, similar TGF-beta 1, in hypertrophic scar compared to normal skin and scar tissue. Overall the results suggest that elevated LTBP-2 may bind and sequester FGF-2 on elastic fibres in fibrotic tissues and modulate FGF-2’s influence on the repair and healing processes.